Distribution of zooplankton in the Jiangsu coastal area: Relationship with the drift path of green algae. (February 2020) - Wang, Xiao; Fan, Shiliang; Xiao, Jie; Li, Yan; Zhang, Xuelei; Wang, Zongling
Abstract: Four cruises were conducted in the Jiangsu coastal area to trace drift paths of green algae from 2009 to 2012. Zooplankton were sampled using shallow-water plankton net (mesh size: 500 μm). Copepods, pelagic larvae, and cnidarians exhibited the highest species diversities and that of cnidarians increased over time. Calanus sinicus, Aidanosagitta crassa, Labidocera euchaeta, and euphausiid larvae were consistently the dominant taxa. Zooplankton abundance was the highest in 2010, with a mean of 359.85 ± 309.58 individuals/m 3, while greatest biomass was found in 2012, with a mean of 379.22 ± 361.55 mg/m 3 ; no interannual differences were observed. The Shannon diversity and Pielou evenness decreased from nearshore to offshore in 2009 but not in 2010. The distribution of dominant endemic taxa changed with that of green algae: higher abundances were limited to the nearshore environment or parallel to the coastline in 2010, while in 2009, higher abundances were found in the offshore drift path of green algae. Highlights: The dominant taxa were constant but cnidarian diversity increased from 2009 to 2012. Zooplankton abundance and biomass showed no interannual variation. The distribution of endemic dominants was consistent with that of green algae.